Finland : 2019 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation highlights that Finland's economy has performed well over the past three years, however, has slowed in 2019. There are some vulnerabilities in household finances, and productivity growth remains weak, with trend growth also constrained by adverse demographics. A new coalition government targets greater social support and inclusion, higher employment, carbon neutrality by 2035, and a balanced budget by 2023. A key challenge is to balance plans to increase spending with the need to maintain fiscal buffers. The fiscal expansion is expected to provide useful cyclical support in the short run, but offsetting measures will be required to ensure the structural balance reaches the government's medium-term target. The government aims for a substantial increase in employment, but the effectiveness of the proposed wage subsidies is unclear. Alternatively, incentives from tax and benefit schedules could be improved, especially for younger women, older workers, and those out of the workforce. Risks in the banking system remain low overall, but some types of lending are increasing household vulnerabilities. The recent recommendation to limit the ratio of household debt to income is both sensible and in line with steps taken in many other countries.